Menstrual dignity project: Guaranteeing access to menstrual health to the community of the São Carlos do Jamari district, Rondônia - Souza, Bruno Gabriel Rodrigues; Sodré, Hávila Pacífico; Silva, Maria Antônia Zeri de Sousa; Moura, Nínive Andreia Garcia (Seven Editora, 2023)
Menstruation is a physiological and cyclical process that occurs during the woman’s reproductive period and results in endometrial shedding and bleeding. It is a natural process of the female organism and can represent a social and public health problem when a portion of women do not have access to hygiene products necessary to control menstrual flow, such as a simple intimate absorbent. Menstrual poverty reflects, among other reasons, the lack of financial resources that make it difficult to acquire these products as well as the lack of information about the menstrual cycle. The negligence of the State, in providing resources or the free distribution of these items, encourages voluntary social projects, such as the one carried out by students from the Pharmacy course at the São Lucas University Center. On the occasion, intimate pads were distributed to women from the riverine community located in the São Carlos do Jamari district. DOI: https://doi.org/10.56238/thebestiimulti2022-005